Moving Nigeria forward : the development planning approach - Adeyemi, Olusola (Ibadan : Ibadan University Press, 2001)
The book reviews some of the key issues and problems that have tasked development planning efforts since Nigeria's independence, including the grave policy and institutional lapses that have inhibited successive attempts to achieve effective resource management. It also highlights a proposed country's appropriate programme direction for meeting its developmental challenges.
Includes bibliographical references and index.
oif 31/07/14, opc30/03/15, rpm 02/09/16, ijb 06/02/2019
Loan
Keywords: Economic history; Nigeria